(untitled) (American Journal of Islam and Society, 2009)
The book under consideration deals with Babism and Shaykhism, two religiousmovements of nineteenth-century Iran.According toMacEoin, they are principally of note in that they were the precursors of the Baha’i faith. The book consists of the author’s Ph.D. thesis on the emergence of Babism from Shaykhism (completed in 1979, 250 pages); nine articles subsequently published in various journals and books, mainly on different aspects of Babism; seven articles written for the Encyclopedia Iranica; a conference paper; and the author’s translation of the first one-and-a-half chapters of the Bab’s Persian-language Bayan. Almost all of this material is available on-line (for the Ph.D. thesis, see www.h-net.org/ bahai/diglib/books/K-O/M/maceoin/ FROMSHAYKHISMTOBABISM.pdf). As such, this book does not constitute new research and must be regarded more as a retrospective on one scholar’s work. This leads to two questions: For whom is this work intended and how should one review such a book – should one evaluate it on the basis of these works’ value at the time they were published or now? ...